IJCM_398A: A cross-sectional study on morbidity patterns and health behavior among construction workers in Mangalore - Rekha T; Singh Vibhu Pratap; Harigovind P; Baker Abu; Rahim Rebin M.; Prateeksh B.K; Rahul K; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Introduction: The construction industry is one of the most stable growing industries in the developing world. In India, it is the largest economic activity after agriculture. Since it is a labor-intensive industry, it consists of organized, unorganized, skilled, and unskilled labor. Morbidity is departure from a state of physical or psychological well-being, resulting from disease, illness, injury, or sickness, especially where the affected individual is aware of his or her condition which is more common among these workers. This study aims to assess the morbidity Pattern and health behavior among construction workers in a coastal block of Karnataka state. Methodology: This community based cross-sectional study was conducted among 230 manual labor workers at different construction sites in Mangalore. Data was collected using interview schedule and analyzed using SPSS version 24. Results were expressed as proportions using appropriate tables and graphs. Chi-square test will be used and P < 0.05 was considered as statistically significant. Results: In the study majority were males aged 19-29 years, Hindu by religion 84%, and unmarried, with minimum of primary educational qualification and work experience of 1-5 years. The most prevalent morbidity was Musculo skeletal disorders which manifest as constant arthralgia, myalgia followed by ophthalmic manifestation like refractive errors. Hypertension was notable, with communicable diseases like Malaria being common morbidities. Tobacco and alcohol consumption were prevalent, but knowledge on preventive measures against mosquito bites and personal hygiene practices were limited. Safety precautions at construction sites were evident as it is mandatory. Conclusions: The study highlighted prevalent morbidity patterns among construction workers in Mangalore, which seek immediate remedial measures. Improving awareness and intervention regarding the health risks associated with tobacco and alcohol consumption pose significant challenges but are crucial for enhancing workers' well-being aa well as hygiene practices.